Gesture–speech physics in fluent speech and rhythmic upper limb movements. Issue 1 (18th December 2020) - Pouw, Wim; de Jonge‐Hoekstra, Lisette; Harrison, Steven J.; Paxton, Alexandra; Dixon, James A.
Abstract: It is commonly understood that hand gesture and speech coordination in humans is culturally and cognitively acquired, rather than having a biological basis. Recently, however, the biomechanical physical coupling of arm movements to speech vocalization has been studied in steady‐state vocalization and monosyllabic utterances, where forces produced during gesturing are transferred onto the tensioned body, leading to changes in respiratory‐related activity and thereby affecting vocalization F0 and intensity. In the current experiment ( n = 37), we extend this previous line of work to show that gesture–speech physics also impacts fluent speech. Compared with nonmovement, participants who are producing fluent self‐formulated speech while rhythmically moving their limbs demonstrate heightened F0 and amplitude envelope, and such effects are more pronounced for higher‐impulse arm versus lower‐impulse wrist movement. We replicate that acoustic peaks arise especially during moments of peak impulse (i.e., the beat) of the movement, namely around deceleration phases of the movement. Finally, higher deceleration rates of higher‐mass arm movements were related to higher peaks in acoustics. These results confirm a role for physical impulses of gesture affecting the speech system. We discuss the implications of gesture–speech physics for understanding of the emergence of communicative gesture, both ontogenetically and phylogenetically. Abstract : The biomechanical physical coupling of arm movements to speech vocalization has been studied in steady‐state vocalization and monosyllabic utterances. We extend this previous work to show that gesture–speech physics also impacts fluent speech, and we discuss the implications of gesture–speech physics for understanding of the emergence of communicative gesture, both ontogenetically and phylogenetically.